Essentials of Human Genomics - Boyle, Alyssa (United States : c, 2021)
The complete set of an organism's DNA is known as a genome. Human genomics is an interdisciplinary biological field that focuses on the evolution, structure, mapping, functioning and editing of human genomes. It also deals with the application of genomic approaches to enhance the understanding of human disease, variable drug reaction and drug discovery. Human genomes consist of DNA within cell nuclei and a small DNA molecule within individual mitochondria. These are classified as the nuclear genome and the mitochondrial genome. One of the primary goals of human genomics is the collective characterization of all of person's genes as well as their relations with each other. The topics included in this book on human genomics are of utmost significance and bound to provide incredible insights to readers. It traces the progress of this field and highlights some of its key concepts and applications. For all readers who are interested in this field, the case studies included in this book will serve as an excellent guide to develop a comprehensive understanding.
Includes index.
Includes bibliographical references.
Keywords: Bioinformatics; Human genome; Genomics -- Data processing